2021
DOI: 10.1186/s13613-021-00896-4
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid phenotypes in severe COVID-19 predict secondary infection and mortality: a pilot study

Abstract: Background De-regulated host response to severe coronavirus disease 2019 (COVID-19), directly referring to the concept of sepsis-associated immunological dysregulation, seems to be a strong signature of severe COVID-19. Myeloid cells phenotyping is well recognized to diagnose critical illness-induced immunodepression in sepsis and has not been well characterized in COVID-19. The aim of this study is to review phenotypic characteristics of myeloid cells and evaluate their relations with the occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…In line with this, it has been found that cells with MDSC features are implicated in COVID-19, and several reports have described the accumulation of potent immunosuppressive M-MDSCs and G-MDSCs in the disease (4,27,28). In fact, a high M-MDSC/monocyte ratio has been associated with secondary infections and death due to the disease (29); the granulocytic subset has also been associated with mortality in severe COVID-19 (7). We aimed to analyze MDSCs, namely, the monocytic (M-MDSCs) and granulocytic (G-MDSCs) subsets, and the lymphocyte subpopulations in patients with severe COVID-19 from admission into the ICU and during the follow-up until discharge or death.…”
Section: Discussionmentioning
confidence: 84%
“…In line with this, it has been found that cells with MDSC features are implicated in COVID-19, and several reports have described the accumulation of potent immunosuppressive M-MDSCs and G-MDSCs in the disease (4,27,28). In fact, a high M-MDSC/monocyte ratio has been associated with secondary infections and death due to the disease (29); the granulocytic subset has also been associated with mortality in severe COVID-19 (7). We aimed to analyze MDSCs, namely, the monocytic (M-MDSCs) and granulocytic (G-MDSCs) subsets, and the lymphocyte subpopulations in patients with severe COVID-19 from admission into the ICU and during the follow-up until discharge or death.…”
Section: Discussionmentioning
confidence: 84%
“…While neutrophil fraction was significantly reduced with UTI treatment , the MDSC fraction was significantly expanded in the UTI group (-1.22, -0.66); p = 0.002]. MDSCs constitute a heterogeneous population of immature myeloid cells that potently suppress immune responses, and is enriched in sepsis ( 42 44 ). However, the regulatory mechanism of MDSC expansion in sepsis is unknown.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically in the respiratory tract, viral destruction of alveolar cells and bronchial epithelial cells, along with mass production of cytokines, leads to pneumonia and, in severe cases, acute respiratory distress syndrome (ARDS) [ 45 , 46 ]. Although the full picture of COVID-19 pathogenesis remains to be investigated, it is now clear that the cytokine and chemokine profile observed in COVID-19 patients promotes profound changes in myeloid cells that appear to be able to determine the outcome of infection [ 5 , 47 ].…”
Section: Overview Of Covid-19 Pathogenesismentioning
confidence: 99%